(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2025)
This work aims to reconstruct the jurisprudential line of the Inter-American Court of Human Rights that combines dignity with the Children´s best interest. To do so, the method of dynamic analysis of jurisprudence and advisory opinions is applied, which allows for the identification of the usual standard or formula used to address the subject matter. Within this framework, the ways in which the Court cites its previous judgments are studied. As a conclusion of the research, it is observed that the standard is outlined based on parameters that are not yet fully defined, consistently citing the advisory opinion where the standard was coined, the content of which is not fully defined, thus enabling its application in different factual scenarios.